The Place for Indigenous Knowledge in a Sport for Development Program - Essa, Mariana (Université d'Ottawa / University of Ottawa, 2019)
This thesis contains two stand-alone articles for which the overall purpose is to learn from the experiences of a non-Indigenous SFD program designed for Indigenous youth, by exploring how the program has dealt with questions of Indigenous knowledge, culture, and worldviews. By looking at how the program officers and managers articulate their experiences and challenges within the different phases of designing, managing and implementing the SFD program, this study examines questions of decolonization, Indigenization, and resurgence. The first article utilizes an Indigenous resurgence lens to explore the challenges of running the Promoting Life Skills in Aboriginal Youth (PLAY) program through the reflective discourses of middle-upper level management staff members. The main objectives of the first article are to 1) explore the perception of the PLAY staff on challenges experienced within program design and development generally, 2) analyze those challenges in light of critical research on SFD, and 3) inform program development with Indigenous youth. In the second article, I examine the experiences and perceptions of the staff and in dealing more specifically with the question of culture and Indigenous knowledge and Indigenization. This article highlights the experiences that occurred during a two-year period of Indigenous leadership, two years after the piloting of the program. The objectives of this article are to 1) consider and examine the place of culture within SFD for Indigenous youth 2) highlight and learn from Indigenous leadership experience in a Western-based program 3) inform program development.
Keywords: Sport for development; Resurgence; Self-Determination; Indigenous Leadership